Cyclic compressive loading induces a mature meniscal cell phenotype in mesenchymal stem cells with an atelocollagen-based scaffold - Oyama, Shohei; Kanamoto, Takashi; Ebina, Kosuke; Etani, Yuki; Hirao, Makoto; Goshima, Atsushi; Otani, Shunya; Hikida, Minami; Yamakawa, Satoshi; Ito, Shohei; Okada, Seiji; Nakata, Ken (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Biomechanical stimulation is reportedly pivotal in meniscal regeneration, although its effect on mesenchymal stem cell (MSC) meniscal differentiation remains elusive. In this study, we investigated how cyclic compressive loading (CCL) could impact MSCs using three-dimensional cultures in atelocollagen-based meniscal substitute (ACMS). Methods: We extracted MSCs from the meniscus, synovium, and articular cartilage, cultured them in three-dimensional cultures, and exposed them to CCL for 7 days. We then compared the transcriptomes of MSCs treated with and without CCL. Results: Our RNA-seq analysis revealed that CCL induced significant transcriptome changes, significantly affecting chondrocyte-related genes, including SOX9, TGFB1, and PRG4 upregulation. CCL induced transcriptional differentiation of meniscus progenitors toward mature meniscal cells. Conclusion: This study unveils the potential of mechanical stress in promoting MSC meniscal differentiation within ACMS. Our investigations provide new insights for mechanisms underlying meniscal regeneration with ACMS.